Modelling and Design Analysis for Nonlinear 3D Dynamic Simulation of Triangular Microspring for MEMS based SAM (International Journal of Engineering and Computer Science, 2016)
This paper reports the design and modelling of triangular shaped microspring which is proposed to be used for munition purpose. The simulation results are obtained for Safe and Arm mechanism for different ‘g’ for MEMS based Rocket SAM. Design for MEMS based technology for Rocket SAM chip is structured in such a way that it has both movable and non-movable parts which utilizes mechanical properties, structural properties and material properties that may be and may not be electronically controlled. The design proposed for Rocket SAM in this research is aimed to achieve reliability, safety and cost effectiveness for mass-production. Our motive is to design, simulate and derive its results using metal alloy MEMS based Rocket SAM using SOLIDWORKS Multiphysics software is used which propounds a prodigious environs to solve this problem. Thus, this research presents the design analysis, modelling and nonlinear 3D dynamic simulation of MEMS based metal alloy for Rocket SAM using SOLIDWORKS Multiphysics GUI tool.